Progress : the sound of action - Ow, Nicolas Joseph Ying Jie (2019)
This report will document the entire process of the sound plan throughout pre-production, location sound recording, and audio post-production in the making of the film, “Progress”. The first part of the report will cover the pre-production planning, and go into detail of the steps taken leading up to production sound recording. Following which, the report will delve into the positive and negative experiences of location sound recording, along with the solutions developed to tackle these challenges whilst on set. The final portion of the report will describe the post-production process and workflow for sound. This portion covers all aspects from the creation of sound effects up to the final mixing of the entire film.